Psychological impact of revealing a diagnosis of lung cancer to patients in China - Qian, Huimin; Hou, Lili (Journal of Thoracic Disease, 2016)
Background: In conventional Chinese culture, awareness of a malignant disease is believed to increase a patient’s psychological pressure, leading to anxiety or depression. But this notion is in conflict with the patient’s right to receive information about their own disease. Methods: This study is to investigate whether disclosure of diagnosis increases the level of anxiety or depression in patients diagnosed with lung cancer. Seventy patients who underwent lung resection and diagnosed with lung cancer postoperatively were divided into two groups—the disclosed group (n=35) and the undisclosed group (n=35), depending on the awareness of their diagnosis, as decided by their consigned family members. All patients were asked to fill in a form to evaluate their level of anxiety and depression before discharge. Results: Disclosure of diagnosis did not affect the degree of anxiety or depression in patients with lung cancer (P>0.05). Age ≤50, relatively more advanced stage (stage II as compared with Stage I) of disease, extensive surgery and major postoperative complication were risk factors of anxiety (P